Validity and Practicality of E-Module Model Inquiry Based Online Learning to Improve Student Competence - Prima Nora Ananda; Usmeldi Usmeldi (Postgraduate, University of Mataram, 2023)
The advent of the 4.0 revolution has had an impact on the education industry. Postgraduate skills need to be able to manage technology, be connected and digitally resilient. Therefore, there is a need to update and find suitable learning models and media to meet these needs. The purpose of this study was to determine the effectiveness and utility of an inquiry-based e-learning model of e-modules for enhancing student competency. This type of research employs the development of the Plomp model which consists of three stages, namely Preliminary research, Prototyping Phase, Assessment Phase. The research conducted was limited to validity and practicality tests. The instruments used were validity and practicality questionnaires.Â The validity become evaluated the use of Aiken's V scale and the practicality was evaluated using Likert scale. Based on data analysis, the results of validity testing by experts on the substance of the material obtained a value of 0.84, visual communication display 0.94, learning design 0.81 and software use 0.78 which is in the valid category. Then the practical results by teachers were 89.71 and by students were 87.28. This suggests that the e-module developed is legitimate and realistic for use in in addition research.